A Review of Hydraulic Fracturing Simulation - Chen, Bin; Barboza, Beatriz Ramos; Sun, Yanan; Bai, Jie; Thomas, Hywel R; Dutko, Martin; Cottrell, Mark; Li, Chenfeng (Archives of computational methods in engineering, 2022)
Along with horizontal drilling techniques, multi-stage hydraulic fracturing has improved shale gas production significantly in past decades. In order to understand the mechanism of hydraulic fracturing and improve treatment designs, it is critical to conduct modelling to predict stimulated fractures. In this paper, related physical processes in hydraulic fracturing are firstly discussed and their effects on hydraulic fracturing processes are analysed. Then historical and state of the art numerical models for hydraulic fracturing are reviewed, to highlight the pros and cons of different numerical methods. Next, commercially available software for hydraulic fracturing design are discussed and key features are summarised. Finally, we draw conclusions from the previous discussions in relation to physics, method and applications and provide recommendations for further research.